Role of metastasis-induced protein S100A4 in human non-tumor pathophysiologies. Issue 1 (December 2017) - Fei, Fei; Qu, Jie; Li, Chunyuan; Wang, Xinlu; Li, Yuwei; Zhang, Shiwu
Abstract S100A4, an important member of the S100 family of proteins, is best known for its significant role in promoting cancer progression and metastasis. In addition to its expression in tumors, upregulation of S100A4 expression has been associated with various non-tumor pathophysiology processes. However, the mechanisms underlying the role of S100A4 remain unclear. Activated "host" cells (fibroblasts, immunocytes, vascular cells, among others) secrete S100A4 into the extracellular space in various non-tumor human disorders, where it executes its biological functions by interacting with intracellular target proteins. However, the exact molecular mechanisms underlying these interactions in different non-tumor pathophysiologies vary, and S100A4 is likely one of the cross-linking factors that acts as common intrinsic constituents of biological mechanisms. Numerous studies have indicated that the S100A4-mediated epithelial–mesenchymal transition plays a vital role in the occurrence and development of various non-tumor pathophysiologies. Epithelial–mesenchymal transition can be categorized into three general subtypes based on the phenotype and function of the output cells. S100A4 regulates tissue fibrosis associated with the type II epithelial–mesenchymal transition via various signaling pathways. Additionally, S100A4 stimulates fibroblasts to secrete fibronectin and collagen, thus forming the structural components of the extracellular matrix (ECM) and stimulating their deposition in tissues, contributing to the formation of a pro-inflammatory niche. Simultaneously, S100A4 enhances the motility of macrophages, neutrophils, and leukocytes and promotes the recruitment and chemotaxis of these inflammatory cells to regulate inflammation and immune functions. S100A4 also exerts a neuroprotective pro-survival effect on neurons by rescuing them from brain injury and participates in angiogenesis by interacting with other target molecules. In this review, we summarize the role of S100A4 in fibrosis, inflammation, immune response, neuroprotection, angiogenesis, and some common non-tumor diseases as well as its possible involvement in molecular pathways and potential clinical value.